Multi-level analysis of motor actions as a basis for effective coaching in virtual reality - Hülsmann, F.; Frank, C.; Schack, T.; Kopp, S.; Botsch, M. (Proceedings of the 10th International Symposium on Computer Science in Sports (ISCSS), 2016)
In order to effectively support motor learning in Virtual Reality, real-time analysis of motor actions performed by the athlete is essential. Most recent work in this area rather focuses on feedback strategies, and not primarily on systematic analysis of the motor action to be learnt. Aiming at a high-level understanding of the performed motor action, we introduce a two-level approach. On the one hand, we focus on a hierarchical motor performance analysis performed online in a VR environment. On the other hand, we introduce an analysis of cognitive representation as a complement for a thorough analysis of motor action.